Biodesulphurization of fossil fuels: energy, emissions and cost analysis. Issue 43 (14th May 2015) - Alves, L.; Paixão, S. M.; Pacheco, R.; Ferreira, A. F.; Silva, C. M.
<x xml:space="preserve">Abstract</x> BDS and HDS as a combined technology towards ultra low sulphur fuels.